Impacts of the COVID-19 pandemic on access to sexual and reproductive health services for women and gender-diverse people with disabilities in Canada: a qualitative study - Meredith Evans; Alexandra Rego; Nkem Ogbonna; Kate Welsh; Sidrah K. Zafar; Lucy C. Barker; Anne Berndl; Janice Du Mont; Yona Lunsky; Amy McPherson; Lesley A. Tarasoff; Ashley Vandermorris; et al. (Sexual and Reproductive Health Matters)
The COVID-19 pandemic has had a detrimental impact on sexual and reproductive health (SRH) and rights globally. However, little is known about the experiences of people with disabilities accessing SRH services during the COVID-19 pandemic. In this community-engaged qualitative study, we examined COVID-related impacts on access to SRH services for people with disabilities. We interviewed 61 women and gender-diverse people in Canada from May 2022 to March 2023. Informed by disability reproductive justice, we identified four major themes through constructivist analysis. First, COVID-related changes to SRH service delivery disrupted access to care and caused disability-related health implications. Second, pandemic response measures changed SRH service accessibility: in-person accessibility barriers were amplified, new in-person accessibility barriers were introduced, and the transition to telehealth exacerbated, as well as mitigated, accessibility barriers. Third, COVID-related social changes (e.g. lockdowns) had disability-related SRH and rights implications. Fourth, disabled people recommended improving SRH services by enhancing funding, provider training, information and communication, disability accommodations, representation, and comprehensive community engagement. Cutting across these themes were disproportionate negative impacts of the COVID-19 pandemic on access to SRH services for racialised women and gender-diverse people with disabilities. Failure to ensure SRH and rights for women and gender-diverse people with disabilities during the COVID-19 pandemic undermined disability reproductive justice. Comprehensive disability community engagement is necessary to inform accessible SRH services and policies, both during and beyond a pandemic.